ETHIC AND THE AFFECTING FACTORS: INSIGHTS FROM SHARIA ACCOUNTING STUDENTS - Istiariani, Irma (Journal of Islamic Accounting and Finance Research, 2020)
Purpose - The purpose of this study was to explore many factors that affect the accounting students? ethics such as intellectual, emotional and spiritual quotients.Method - The data of this study were obtained from questionnaires. The sample consists of 90 Sharia Accounting students who studied at the FEBI UIN Walisongo. The sample was collected by purposive sampling method and it was analysed with SPSS.  Result - The result shows that there are three factors affecting the students? ethics. They are intelligence, emotional and spiritual quotients. The emotional and spiritual quotients have the positive effect on students? ethics. The intelligence quotients has a negative effect on the students? ethics.Implication - This study suggests to improve students? emotional and spiritual quotients for better students? ethics quality.Originality - This research is the first study that researched about the ethical students in Sharia Accounting students.